A Meta-Analysis of Influencers of Automobile Purchase Intention of Customers and Evolution of the Automobile Consumer Behavior From TCB - Anuradha Banerjee; Basav Roychoudhury; Bidyut Jyoti Gogoi (Journal of Advanced Transportation)
Several studies have explored the antecedents of automobile purchase intention (API) of customers across different geographical regions of the world. These have, however, come up with contradictory findings about the polarities of effects of some antecedents, as well as about some of their differences across countries. We were motivated by these contradictions and differences to carry out a meta-analysis on API. In the study, we considered articles from peer-reviewed databases such as Google Scholar, Web of Science, Scopus, ScienceDirect, and Wiley. Our study and analysis of the full texts of 136 articles yielded 64 antecedents. The specific polarity of effect (positive or negative) on API is established for 59 of these antecedents, whereas the same remained undetermined for the rest five. We identified these as research gaps, the areas yet to be convincingly explored. Furthermore, based on the absence of publication bias and the 95% CI of impact not crossing the line of null effect, we enlisted 20 antecedents spread across the different stages of the automobile purchase decision process, which we propose to add to the theory of consumer behavior as the automobile consumer behavior (TACB). Our study can help managers to better understand consumer behavior in terms of the discovered antecedents, especially those having a higher impact at a particular stage of the process, and can result in better business decisions.